Using storytelling with adult EFL learners: an enriching classroom experience - Vecino, Adriana (Colombian Applied Linguistics Journal, 2006)
Storytelling has obvious benefits in the development of speaking and listening skills, vocabulary and memory abilities. It also nurtures reading and writing skills and offers learners opportunities to increase their confidence. Given the great value in employing storytelling as a support when learning a foreign language, I decided to use this technique with one of my adult EFL classrooms and observe the benefits and possible constraints. This paper presents the theoretical foundations that underlie my pedagogical innovation as well as the results obtained from its implementation. In addition, valuable reflections invite teachers to integrate storytelling into their English lessons and explore their use with adult learners.